Impact of the Didactic Manual "Creating and Recreating" on the development of linguistic intelligence in fifth grade students: An innovative approach in basic education (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
The research focused on exploring the impact of the development and application of an innovative didactic manual entitled "Creating and Recreating" on the development of linguistic intelligence of fifth grade students of basic education in the Eloy Alfaro Educational Unit of Alausi canton. The methodology was of quasi-experimental design, with a mixed and explanatory approach. The interactions of 18 students were observed during the application of the manual to obtain a detailed understanding of their participation and reactions. In addition, structured surveys were designed to collect data on the change in the 18 students' perceptions of linguistic intelligence before and after the application of the manual. The findings consistently indicated a positive impact on multiple dimensions of students' language learning after the application of the didactic manual. There was evidence of a favorable change in the students' interest in and enjoyment of reading, as well as notable transformations in their reading practices and preferences. Particularly noteworthy is the positive impact on semantic interpretation skills and reading comprehension, suggesting that the manual played an integral role in the development of key skills. These results underscore the effectiveness of the pedagogical approach adopted, supporting the relevance of innovative strategies to enhance the learning process and encourage